CHARACTERIZATION OF CENTRAL AND EFFECTOR CD4⁺ MEMORY CELLS IN PSORIASIS - A. V. Kolerova (SPb RAACI, 2021)
Psoriasis is a chronic autoimmune disease in which the skin and joints are involved in the pathological process. It was found that the recurrence of rashes in this disease occurs due to the resident memory cells of the skin. The number of CD4+CCR3+ effector memory cells in peripheral blood correlates with the severity of the disease. Therefore, the aim of our work is to study the phenotype of peripheral blood memory cells in patients with psoriasis.The study included 6 healthy donors: average age – 45.4 (min – 29, max – 55), women – 3, men – 3; 10 patients with psoriasis: women – 4, men – 6, average age – 37.3 (min – 23, max – 57), of which 5 patients with PASI > 10 and 5 patients with PASI < 10. The exclusion criteria for the study were the presence of autoimmune, oncological and hematological diseases, systemic therapy with immunosuppressive drugs for 1 month. Patients signed informed consent to participate in the study. Isolation of peripheral blood mononuclear cells was performed in a density gradient of ficoll-urographin (p = 1.082 g/L). Then cells were stained with fluorochrome-conjugated monoclonal antibodies to surface markers of central (Tcm) and effector (Tem) CD4+ memory cells (CD4, CD45RO, CD197), the α-chain of the IL-7 receptor (CD127), and the γ-chain of the IL-7 receptor (CD132). Statistical analysis of the data obtained was performed using the Statistica 6.0 software package.The percent of Tcm in the peripheral blood of donors was 33.4% (in – 18.2, max – 43.7), Tem – 28.7% (min – 13.6, max – 38.9), in patients with psoriasis: Tcm – 28.65% (min – 13.3, max – 59.6), Tem – 21.5% (min – 9.3, max – 38.6). In the peripheral blood of patients with psoriasis, among the central CD4+ memory cells, the proportion of CD127+CD132- -cells is 26.00%, CD127+CD132+ – 1.69%, CD127+CD132- – 69.00%, CD127- CD132+ – 1.94%. Among effector CD4+ memory cells, the proportion of CD127+CD132- -cells is 23.58%, CD127+CD132+ – 1.18%, CD127+CD132- – 69.84%, CD127- CD132+ – 0.70%. A direct correlation was found between the number of CD127- CD132+ central memory cells and the PASI value (r = 0.639, p < 0.05).In patients with psoriasis, the proportion of central memory cells is higher than in healthy donors, while the number of effector memory cells is lower. A direct correlation was found between the number of central cells expressing the γ-chain of the IL-7 receptor and the severity of the disease. Activated memory cells are characterized by high expression of CD132. It can be assumed that this population of memory cells plays a role in maintaining autoimmune inflammation in patients with this disease, and also participates in the repopulation of skin resident memory cells.